Revisiting herbage sample collection and preparation procedures to minimise risks of trace element contamination - Dahlin, A. Sigrun; Edwards, Anthony C.; Lindström, Bodil E.M.; Ramezanian, Atefeh; Shand, Charles A.; Walker, Robin L.; Watson, Christine A.; Öborn, Ingrid (European journal of agronomy, 2012)
► Trace element contamination may occur at any stage from sample collection to chemical analysis. ► Contamination sources include dust, work surfaces, tools and containers. ► Contamination may be counteracted by precautionary measures during sampling and sample preparation. ► A test of several mills showed high contamination by several elements except from a Ti knife mill. A renewed interest in trace elements (TE), as micronutrients as well as potentially toxic elements, and new options for multi-element analysis has led to an increased number of scientists engaging in TE studies. Accreditation, certification and quality control of TE analyses often applies only to the last step in the sample chain when prepared samples are sent to the laboratory for digestion/extraction and subsequent analysis. However, all stages of the chain from initial sampling to final analysis require an understanding of the specific challenges involved in TE studies and an awareness of the contamination risks as well as approaches to limit these. Contamination can potentially be introduced during all stages of handling and preparation of plant samples, e.g. through dust and the materials that make up the different work surfaces, tools and containers used. Milling devices originally used during preparation of two sets of archived herbage samples were tested to indicate the degree of contamination that can arise from milling. For example, some of the milling devices tested showed effects on several TE concentrations while also increasing the variability between samples. A titanium knife mill which was included for comparison gave the best results, showing no measurable contamination by TE of primary interest, while it allowed a high throughput of samples. To enhance the quality of data on TE in bulky plant material such as herbage and to ensure future usability of newly archived samples, we suggest that field handbooks and sample preparation protocols (where needed) are revised to include precautions against TE contamination in all handling steps. This will ensure reliable data on concentrations of micronutrients and potential toxic TE in plant material.